Donor Lymphocyte Infusions After Allogeneic Stem Cell Transplantation in Acute Leukemia: A Survey From the Gruppo Italiano Trapianto Midollo Osseo (GITMO) - Patriarca, Francesca; Sperotto, Alessandra; Lorentino, Francesca; Oldani, Elena; Mammoliti, Sonia; Isola, Miriam; Picardi, Alessandra; Arcese, William; Saporiti, Giorgia; Sorasio, Roberto; Mordini, Nicola; Cavattoni, Irene; et al. (Frontiers in Oncology, 2020)
We conducted a retrospective multicenter study including pediatric and adult patients with acute leukemia (AL) who received donor lymphocyte infusions (DLIs) after allogeneic hematopoietic stem cell transplantation (HSCT) between January 1, 2010 and December 31, 2015, in order to determine the efficacy and toxicity of the immune treatment. Two hundred fifty-two patients, median age 45.1 years (1.6-73.4), were enrolled from 34 Italian transplant centers. The underlying disease was acute myeloid leukemia in 180 cases (71%). Donors were HLA identical or 1 locus mismatched sibling (40%), unrelated (40%), or haploidentical (20%). The first DLI was administered at a median time of 258 days (55-3784) after HSCT. The main indication for DLI was leukemia relapse ( 73%), followed by mixed chimerism ( 17%), and pre-emptive/prophylactic use ( 10%). Ninety-six patients (38%) received one single infusion, whereas 65 (26%), 42 (17%), and 49 patients (19%) received 2, 3 or ≥ 4 infusions, respectively, with a median of 31 days between two subsequent DLIs. Forty percent of evaluable patients received no treatment before the first DLI, whereas radiotherapy, conventional chemotherapy or targeted treatments were administered in 3%, 39%, and 18%, respectively. In informative patients, a few severe adverse events were reported: grade III-IV graft versus host disease (GVHD) (3%), grade III-IV hematological toxicity (11%), and DLI-related mortality (9%). Forty-six patients (18%) received a second HSCT after a median of 232 days (32-1390) from the first DLI. With a median follow-up of 461 days (2-3255) after the first DLI, 1-year, 3-year and 5-year overall survival (OS) of the whole group from start of DLI treatment was 55%, 39%, and 33%, respectively. In multivariate analysis, older recipient age and transplants from haploidentical donors significantly reduced OS , whereas DLI for mixed chimerism or as pre-emptive/prophylactic treatment compared to DLI for AL relapse and a schedule including more than one DLI significantly prolonged OS . This GITMO survey confirms that DLI administration in absence of overt hematological relapse and multiple infusions are associated with a favorable outcome in AL patients. DLI from haploidentical donors had a poor outcome and may represent an area of further investigation